Quantifying the Agyrotropy of Proton and Electron Heating in Turbulent Plasmas - Yan Yang; Francesco Pecora; William H. Matthaeus; Sohom Roy; Manuel Enrique Cuesta; Alexandros Chasapis; Tulasi Parashar; Riddhi Bandyopadhyay; D. J. Gershman; B. L. Giles; J. L. Burch (The Astrophysical Journal, 2023)
An important aspect of energy dissipation in weakly collisional plasmas is that of energy partitioning between different species (e.g., protons and electrons) and between different energy channels. Here we analyse pressure–strain interaction to quantify the fractions of isotropic compressive, gyrotropic, and nongyrotropic heating for each species. An analysis of kinetic turbulence simulations is compared and contrasted with corresponding observational results from Magnetospheric Multiscale Mission data in the magnetosheath. In assessing how protons and electrons respond to different ingredients of the pressure–strain interaction, we find that compressive heating is stronger than incompressive heating in the magnetosheath for both electrons and protons, while incompressive heating is stronger in kinetic plasma turbulence simulations. Concerning incompressive heating, the gyrotropic contribution for electrons is dominant over the nongyrotropic contribution, while for protons nongyrotropic heating is enhanced in both simulations and observations. Variations with plasma β are also discussed, and protons tend to gain more heating with increasing β .